Lived experiences of emergency medical personnel in Capricorn District : towards the development of user-led model - Manganyi, Patricia Siphiwe (My University, 2021)
An Emergency Medical Service (EMS) is considered one of the most stressful work environments. Copious literature has demonstrated that emergency service work has an undesirable impact on the health and wellbeing of personnel. In South Africa, research findings described that emergency services personnel are among the highest group of professionals at risk of suffering from job-related stress. In spite of the fact, previous studies have examined the association between critical incidents and Post Traumatic Stress Disorder (PTSD) symptoms including the psychological influence of trauma, a minority studies have explored the EMS personnel’s traumatic experiences and the subsequent coping strategies applied. This study sought to explore and describe the lived experiences of Emergency Medical Personnel in Capricorn District and to develop a user led model for mitigating occupational stress among EMS personnel. The principal aim of this study was achieved through the following objectives; to profile work related stress and the lived experiences of EMS personnel in Capricorn District, to Identify and appraise coping strategies employed by EMS personnel, to establish how accessible and user friendly EAP services are to EMS personnel, to determine the nature of social support (colleagues and supervisors) EMS personnel receive and to develop a user-led model for EMS personnel. This study was rooted in three theories, namely; trauma theory, resilience theory and the strengths perspective theory. The three theories were appropriate in this study to offer a perspective of situation and to analyse the situation under study to provide an understanding into the way in which EMS personnel make sense of their situation of the challenges they come across and make use of the available resources. The three theories interlaced together played a critical role in this study as they both align with building resilience, recognise individual’s innate strengths and coping in the face of hardship. Owing to the inimitability role of the emergency personnel and the services’ work context, the study adopted a qualitative approach. The purpose of the study was exploratory descriptive in nature. Exploring both their experience of critical incidents and the coping strategies employed by them to mitigate work-related stress and traumatic incidents from this qualitative perspective allowed the researcher to employ phenomenological research design for this study. A sample size of 21 emergency employees comprising 7 station managers and 14 EMS personnel) was obtained through purposive sampling technique. Thematic analysis was used to analyse data.  The findings suggest that life in the emergency field can possibly have an undesirable long-term effect on employees’ overall health and welfare and higher risk of PTSD. The distressing incidents were those in which the participants experienced feelings of vulnerability and had no control of the situations. The study established that emergency personnel find it most hard to deal with incidents involving children and colleagues. Emergency personnel suffer from emotional and physical stress owing to high job demands and repeated exposure to traumatic incidents. Regardless of the traumatic nature of emergency work and the inimitable role of emergency personnel, this study discovered that fact several stressors originate from organisational failure such lack of involvement in decision-making process, lack of training and shortage of staff. Unsupportive work environment, Lack of personal and job resources were found to be the extensive contributory factors to the job pressure experienced by which lead to compassion fatigue and exhaustion. It was also discovered the current EAP programme in the Department of Health (DoH) is not known and inaccessible to EMS personnel. The coping strategies utilised by emergency personnel were not adequate to prevent the aftermath of critical incidents. However collegial and social support from supervisors were found helpful in dealing with work-related stress. The study findings revealed that emergency personnel were unaware of the available support services within the DoH in Capricorn District. Collectively, the findings confirm that there is a need for an extensive marketing strategy of the EAP services and the user-led model which will be implemented by the organisation. The researcher recommends that EAP policies should form part of package given to new recruits during induction or orientation programme and diverse marketing strategies should be adopted to familiarise employees with EAP services available to them. The DoH should consider decentralisation of EAP services to enhance accessibility.
Thesis (Ph.D. (Social Work)) -- University of Limpopo, 2021
Keywords: EMS personnel; Occupational stress; Post-Traumatic stress disorder (PTSD); Coping; Job resources; Employee assistance programme (EAP); Job stress -- South Africa; Stress (Psychology) -- Congresses; Employee assistance program; Emergency Medical Service -- Job stress; Employee Assistance Program Inventory; Post-traumatic stress disorder